A case of hypertensive emergency, primary hypothyroidism and large pericardial effusion with early tamponade. Issue 1 (July 2018) - Chiu, Michael H.; Sharma, Nakul C.
Abstract: Thyroid hormones and the cardiovascular system are strongly intertwined with known risk of coronary disease, atrial fibrillation, and cardiomyopathy. Pericardial effusions are commonly seen in cases of severe hypothyroidism, however large to massive pericardial effusions with cardiac tamponade are exceptionally rare. We report a case of a patient presenting with hypertensive emergency and a concomitant diagnosis of primary hypothyroidism with a large pericardial effusion and early echocardiographic features of tamponade. Following pericardiocentesis, hypertension management, and thyroid replacement therapy the patient's symptoms improved with no recurrence of pericardial effusion. <Learning objective: Hypothyroidism is a common medical comorbidity with many clinical manifestations and cardiovascular effects including hypertension. Pericardial effusion is a known complication of hypothyroidism, however cases of massive effusion and tamponade are rare. Management of large effusions is unclear, with some patients treated with thyroid supplement and others requiring pericardiocentesis.>